An Index Number Formula Problem : The Aggregation of Broadly Comparable items - Silver, Mick (IMF Working Papers; Working Paper ;, 2009)
Index number theory informs us that if data on matched prices and quantities are available, a superlative index number formula is best to aggregate heterogeneous items, and a unit value index to aggregate homogeneous ones. The formulas can give very different results. Neglected is the practical case of broadly comparable items. This paper provides a formal analysis as to why such formulas differ and proposes a solution to this index number problem.